L’autorité à l’école : entre enseignants et élèves, une norme relationnelle ? - Marie Beretti (Recherches en Éducation)
Regarding authority, the norm requires some practices as usual and some others as exceptional. But within the practices of authority, the norm involves a more or less clear and precise definition of what is a good authority as a human behaviour, as a professionnal behaviour, and, at the same time, teachers authority seecks to produce or maintain certain expectations towards the pupils: « required » behaviors which comes from the interiorization of another kind of norms. Authority, thus, is in double connection with the norm: within its practice, the authority of the teacher is the object of a norm (a professional standard), in the same movement, authority intends to make the pupils follow other norms (social norms). Based on data on the construction of the relationship of authority, collected in an empirical investigation, with classes of third elementary cycle, this article focus on how authority at school, in its required and observable dimensions, emerges as object of a professional standard, and as vector of social norms. In other words, this work will argue how teaching authority is jointly standardized and normative.